Measurement of K⁰S and Λ⁰ production in tt¯ dileptonic events in pp collisions at √s = 7 TeV with the ATLAS detector - Alonso, Francisco (2019)
Measurements of K⁰S and Λ⁰ production in tt¯ final states have been performed. They are based on a data sample with integrated luminosity of 4.6 fb⁻¹ from proton–proton collisions at a centre-of-mass energy of 7 TeV, collected in 2011 with the ATLAS detector at the Large Hadron Collider. Neutral strange particles are separated into three classes, depending on whether they are contained in a jet, with or without a b-tag, or not associated with a selected jet. The aim is to look for differences in their main kinematic distributions. A comparison of data with several Monte Carlo simulations using different hadronisation and fragmentation schemes, colour reconnection models and different tunes for the underlying event has been made. The production of neutral strange particles in tt¯ dileptonic events is found to be well described by current Monte Carlo models for K⁰S and Λ⁰ production within jets, but not for those produced outside jets.